New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae) - Minoura, Kazushige; Masumoto, Masami (Zootaxa, 2016)
Until now, 16 species of Panchaetothripinae in 11genera have been recorded from Japan (Kudo 1992a,b). Recently, however, three further species were found, in the genera Phibalothrips and Caliothrips, and one purpose of this report is to record these two genera from Japan for the first time. The four known species of Phibalothrips occur mainly in the Old World tropics, and are associated with grasses (Mound 2011), whereas the 22 known species of Caliothrips are found in the tropics and subtropics worldwide and feed on a range of different plants including grasses. In this article, P. rugosus, C. punctipennis and C. tongi are newly recorded from Japan, and the male of P. rugosus and second instar larva of C. tongi are described for the first time. Moreover, an identification key to the known species of Phibalothrips is provided. Larval chaetotaxy is based on Heming (1991) and Vierbergen et al. (2010). The specimens studied are deposited in Yokohama Plant Protection Station, Naha Plant Protection Station and the authors’ collection.